Design of a six degree of freedom motion platform for vehicle driving simulator application - Chiew, Yeong Shiong (2009)
This research presents the design and development of a six degree of freedom (6-DOF) motion platform for vehicle driving simulator application in Universiti Teknologi Malaysia. The development processes include reviews of driving simulator technology and design configurations, development of motion platform mathematical modeling and simulation, control algorithm development and validation of simulation results. The motion platform design is based on Stewart platform design configuration. It was mathematically modeled using inverse kinematics to control the kinematic behaviours of the motion platform. A visualisation tool, SimMechanics was used to validate the motion platform motions cues virtually. A Proportional-Integral-Derivative (PID) control algorithm for motion platform actuators control was developed and tested. The motion platform prototype was constructed and interfaced with simulation model through data acquisition system to perform 6-DOF vehicle motion. The prototype was tested and the kinematic performance of the prototype is validated. The results show that the motion platform can be used for driving simulator application.